Factores asociados a la indicación de cesáreas en el hospital Iquitos “César Garayar García”, 2022 - Mendoza Leon, Percy Javier (2025)
Cesarean section is a surgery performed to extract the fetus through an incision in the abdomen and uterus of the mother, whether alive or stillborn, through a laparotomy followed by an incision in the uterine wall, once fetal viability is reached, The present study aims to determine the factors associated with the indication of cesarean sections at the Iquitos Hospital "Cesar Garayar García", 2022 with an observational, descriptive design with a cross-sectional and retrospective, the population group considered in this research will include all women who underwent surgery by cesarean section in the Gynecology Obstetrics area of the "César Garayar García" Hospital in Iquitos throughout 2022, Based on the hospital's surgical procedure registry, a monthly average of 150 cesarean sections is estimated, a sample size of 79 participants was calculated using the formula for finite populations. Inclusion criteria: adult participants of legal age with a cesarean section procedure that occurred in 2022, The data obtained will be recorded in a spreadsheet and processed using SPSS version 22.0, using univariate analysis using indicators of central tendency and dispersion. Using tests such as Student's t test and ANOVA to evaluate differences between groups, and the chi-square test for the analysis of dichotomous variables. A 95% confidence level and 0.05 statistical significance will be used.